Nanoscale periodic gradients generated by laser powder bed fusion of an AlSi10Mg alloy. (1st January 2021) - Lefebvre, Williams; Rose, Grégory; Delroisse, Pauline; Baustert, Eric; Cuvilly, Fabien; Simar, Aude
Abstract: In this study, the formation of a periodic microstructural pattern designed by laser powder bed fusion (LPBF), commonly called selective laser melting (SLM), of an AlSi10Mg alloy is revealed at high resolution using scanning transmission electron microscopy and atom probe tomography. Special attention is paid to the description of non-equilibrium structures and compositional fields resulting from the ultrafast cooling of the LPBF process. Observations reveal the existence of a glass state in eutectic areas, wherein short-range ordering of the diamond-Si structure is observed. The apparent very fast solidification of eutectic regions is found to involve a local strain in adjacent Al cells, which extends up to 100 nm on average. In the supersaturated aluminium solid solution retained by the LPBF process, two populations of clusters are identified, for which the potential role of the selection of hardening phases is discussed. It is proposed that the microstructure of former melt pools outside heat-affected areas is described by the repetition of a periodic microstructural pattern consisting of eutectic regions /strain-hardened Al-crystals /strain-free Al-crystals with a high density of solute-rich clusters. Graphical abstract: A layered nanostructure is produced by laser powder bed fusion of an Al-Si10Mg alloy. Melt pools are formed of repeated Al cells exhibiting a gradient of dislocation density and nano-layers of amorphous-phase enriched in Al and Si containing fine dispersions of diamond-Si nanocrystals. The high solidification rate involves the formation of a high density of solute-rich clusters in Al crystals Unlabelled Image Highlights: The design a periodic microstructural gradient by liquid powder bed fusion in an aluminium alloy is demonstrated The ultrafast cooling allows forming nanoscale features which structure and composition are established. Local strain hardening is evidenced in Al crystal in the vicinity of eutectic areas. Short range ordering of silicon together with the formation of Si nanocrystals is shown in former eutectic areas. Two populations of solute clusters are detected by APT: Mg-rich clusters (containing Si) Mg-free Si-rich clusters.